THE INFLUENCE OF THE MEDIA ON SOCIAL THOUGHT (World Bulletin of Social Sciences, 2025)
This paper analyzes the role of mass media in modern society and its impact on the formation of social consciousness. Social consciousness refers to people's views, evaluations, and ways of thinking about events, social issues, and values within society. As a means of disseminating information, mass media directly influences individuals' worldview, their decisions, and their attitudes toward various social processes. The study examines different types of media, such as the press, television, the internet, and social networks, highlighting both their positive and negative aspects. In conclusion, the paper provides recommendations and methods for shaping social consciousness on a healthy foundation through the use of mass media.